Migration, labour markets and embeddedness: the social constraints of the international migration of labour - Peixoto, João (2010)
It is a widely known phenomenon that labour is one of the less mobile factors of production. As opposed to capital, the main geographical tendency of this factor is that of inertia. Even when international trends are economically dominant, such as the constitution of world economies or the present globalisation, the result is an intense circulation of capital (and, naturally, goods and services) and, in contrast, a sharp stability of local (and national) labour forces. Social and cultural differences among populations, the ever-present risks of migration and political resistance to mobility are the most cited reasons for the inertia of labour movements. These types of obstacles boldly contrast with the powerful forces, either from the macro (economies) or micro (individuals) side, which promote migration. Such forces include the widespread inequalities of income, job opportunities and chances of social mobility. Indeed, labour markets appear to be highly "social" in nature and react in a complex way to their multiple determinants. As a result, social ties often prevent the mobility of the human factor and explain the rigidity to migrations. The aim of this paper is to list the determinants of migration and immobility, to examine their particular strengths and to discuss the possible ways in which this spatial inertia is changing.